Temporal and Geographic Variation in the Incidence of Alzheimer's Disease Diagnosis in the US between 2007 and 2014. Issue 2 (3rd December 2019) - Kirson, Noam Y.; Meadows, Eric S.; Desai, Urvi; Smith, Brian P.; Cheung, Hoi Ching; Zuckerman, Peter; Matthews, Brandy R.
Abstract : OBJECTIVES: Our aim was to describe the incidence of Alzheimer's disease (AD) in the United States, overall and by geographic region. DESIGN: We conducted retrospective analyses of administrative claims data for a 5% random sample of US Medicare beneficiaries aged 65 years or older. AD incidence, defined as a diagnosis for AD ( International Classification of Disease, Ninth Revision, Clinical Modification code 331.0×) in a given year, with no AD diagnosis in the beneficiary's entire medical history, was estimated for each calendar year between 2007 and 2014. Beneficiaries were required to be enrolled in Medicare for the calendar year of evaluation as well as the preceding 12 months. In addition, a cross‐sectional assessment of geographic variation in AD incidence was conducted for 2014. For each population area (specifically, core‐based statistical area, as defined by the US Census Bureau), AD incidence was estimated overall, as well as adjusted for differences in underlying patient demographics and metrics of access to care and quality of care. Changes in AD incidence from 2007 were also estimated. SETTING: US fee‐for‐service Medicare. Participants: US Medicare beneficiaries aged 65 years or older with no history of AD. RESULTS: Overall, the diagnosed incidence of AD decreased over time, from 1.53% in 2007 to 1.09% in 2014; trends were similar for most population areas. In 2014, the rates of AD incidence ranged from 0% to more than 3% across population areas, with the highest observed incidence rates in areas of the Midwest and the South. Statistical models explain little of the geographic variation, although following adjustment, the incidence rates increased the most (in relative terms) in rural areas of western states. CONCLUSION: Our findings are consistent with previously reported estimates of incidence of AD in the United States and its recent declining trend. Additionally, the study highlights the considerable geographic variation in the incidence of AD in the United States and suggests that further research is needed to better understand the determinants of this geographic variation. J Am Geriatr Soc 68:346–353, 2020